Pesan Dakwah Pada Buletin Jum - Haryanto, Haryanto (Jurnal Studi Agama dan Masyarakat, 2016)
Bulletin Friday Himma as one of the media propaganda Islamiyah in the State Islamic Institute ( IAIN ) Palangkaraya and tried to convey a message of propaganda to the whole society , especially students in IAIN Palangkaraya. Content analysis method (content analisys ) , with research focusing on the edition of July to December 2015. The results showed that , Bulletin Himma Friday IAIN Palangkaraya contains all categories of propaganda messages that creed , Shari'ah and Morals . Results of percentage and frequency of occurrence , the message Ahklak slightly more dominant than Sya'riah and creed . Message ahklak get the largest percentage , yaitu : 44% more dominant discusses the character of the fellow human being ( 36.36 % ) , while the shari'a is 36 % more dominant discusses aspects of worship ( 100 % ) and the faith of 20% more dominant discusses aspects of the Faith in Allah SWT ( 100 % ) . Judging from the results can be seen that the percentage Bulletin Himma Friday IAIN Palangkaraya want improved ahklak or behavior for the better in the running of daily life , especially for fellow human beings